A balancing act for breast cancer? Everolimus for hormone receptor positive patients - Wheeler, Stephanie B; Reeder-Hayes, Katherine; Meyer, Anne-Marie (Translational Cancer Research; Vol 1, No 2 (August 01, 2012): Translational Cancer Research, 2012)
Recent results from a Phase III randomized trial comparing everolimus [a mammalian target of rapamycin (mTOR) inhibitor] plus exemestane versus placebo plus exemestane provide encouraging evidence of a new option for treatment of advanced, hormone receptor positive (HR+) breast cancer (1). Oral endocrine therapy (ET) is the first line therapeutic strategy of choice for most women with metastatic HR+, Her2 negative breast cancer (2).